MitraClip therapy in patients with acute severe mitral regurgitation. (25th November 2020) - Turyan Medvedovsky, A; Tahiroglu, I; Tonchev, I; Planer, D; Danenberg, H.D; Beeri, R; Shuvy, M
Abstract: Background: There is a lack of data to support the optimal management of high-risk patients with acute severe mitral regurgitation (MR). The role of the MitraClip implantation in treatment of acute severe mitral regurgitation (MR) is undetermined. Methods: We screened all patients who underwent MitraClip implantation at the Hadassah Medical Center between October 2015 and December 2019. We evaluated immediate, 30-day and 1-year outcomes after the procedure. We evaluated patients with severe MR due to ruptured cord because of degenerative disease and acute-on-chronic functional MR due to ischemic (after a recent myocardial infarction (MI)) or non-ischemic etiology (secondary to decompensated HF). Results: From a cohort of 151 patients, who underwent MitraClip implantation in our center, we identified 35 patients (23.2%) with acute severe mitral regurgitation (4+) and decompensated refractory heart failure. Patients' mean age was 74.15 years, 66.9% - were males. One, 2, or 3 clips were implanted. Reduction of MR from 4+ to 1+ was achieved in 34 patients (66.7%). Twenty-eight patients (80%) had acute-on-chronic severe MR and refractory heart failure including 6 cases after recent MI, other 7 patients presented with heart failure and acute severe MR secondary to ruptured cord due to degenerative disease. After MitraClip implantation, reduction of MR severity was achieved in all patients. Seven patients were withdrawn from intravenous therapy and intra-aortic balloon pump 2–3 days after the procedure. Four patients died during hospitalization, three of them due to sepsis. 30-day follow-up showed improvement of NYHA functional class and a tendency toward improvement in left ventricle systolic function with signs of reverse remodeling. Nevertheless, we observed high 30-day and 1-year mortality rate (11.4 and 23.8% respectively). Conclusions: MitraClip therapy could be an alternative option for treatment of patients with acute and acute-on-chronic severe MR of ischemic and non-ischemic etiology. Funding Acknowledgement: Type of funding source: None